Theoretical and Experimental Study of Spectral Selectivity Surface for Both Solar Heating and Radiative Cooling. (3rd August 2015) - Hu, Mingke; Pei, Gang; Li, Lei; Zheng, Renchun; Li, Junfei; Ji, Jie
Abstract : A spectral selectivity surface for both solar heating and radiative cooling was proposed. It has a high spectral absorptivity (emissivity) in the solar radiation band and atmospheric window band (i.e., 0.2~3  μ m and 8~13  μ m), as well as a low absorptivity (emissivity) in other bands aside from the solar radiation and atmospheric window wavelengths (i.e., 3~8  μ m or above 13  μ m). A type of composite surface sample was trial-manufactured combining titanium-based solar selective absorbing coating with polyethylene terephthalate (TPET). Sample tests showed that the TPET composite surface has clear spectral selectivity in the spectra of solar heating and radiation cooling wavelengths. The equilibrium temperatures of the TPET surface under different sky conditions or different inclination angles of surface were tested at both day and night. Numerical analysis and comparisons among the TPET composite surface and three other typical surfaces were also performed. These comparisons indicated that the TPET composite surface had a relative heat efficiency of 76.8% of that of the conventional solar heating surface and a relative temperature difference of 75.0% of that of the conventional radiative cooling surface, with little difference in cooling power.